Rural–Urban Disparities in Pregnancy Intentions, Births, and Abortions Among US Adolescent and Young Women, 1995–2017 - Sutton, April (Am J Public Health, 2019)
Objectives. To examine rural–suburban–urban disparities in intendedness and resolution of first pregnancies among adolescent and young women (aged 15–19 and 20–24 years) across racial/ethnic backgrounds in the United States. Methods. We used the National Survey of Family Growth and pooled pregnancy files from 2002 through the 2015–2017 surveys. We report baseline rural–suburban–urban disparities in first pregnancy intention and outcomes. We used multinomial logistic regression to estimate these disparities, accounting for sociodemographic background, religious upbringing, and other factors. Results. The first adolescent pregnancies of rural women were more likely to be unintended and end in live birth relative to their urban counterparts. Disparities were most striking among Black adolescents, with about 60% of first adolescent pregnancies among rural Black women being unintended and ending in live birth (urban: 51%). Newly collected state health department data on rural and urban adolescent births and abortions corroborate the findings from the National Survey of Family Growth. Conclusions. Rural–urban differences in the share of first adolescent pregnancies ending in live births are not accounted for by pregnancy intention or confounding individual-level characteristics. Future research should explore the role of structural barriers, including access to family planning and abortion services.